2022
DOI: 10.1371/journal.pone.0269277
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in hypothyroid patients: A systematic review and meta-analysis

Abstract: Introduction Hypothyroidism may be associated with changes in the autonomic regulation of the cardiovascular system, which may have clinical implications. Objective To conduct a systematic review and meta-analysis on the impact of hypothyroidism on HRV. Materials and methods PubMed, Cochrane, Embase and Google Scholar were searched until 20 August 2021 for articles reporting HRV parameters in untreated hypothyroidism and healthy controls. Random-effects meta-analysis were stratified by degree of hypothyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 85 publications
(127 reference statements)
0
2
0
1
Order By: Relevance
“…As the nLF and LF/HF ratios are indicators of the relative level of sympathetic activity compared with parasympathetic activity, the SNS is activated more than PNS as the TSH level goes to both ends of the euthyroid TSH range. Brusseau et al [ 51 , 52 ] reported that the nLF and LF/HF ratio increased in hyperthyroid patients with decreased TSH levels, while the nLF and LF/HF ratio increased in hypothyroid patients with increased TSH levels. Although the results of the study did not enlist euthyroid patients, they are consistent with the opposite trend in the nLF and LF/HF ratio in the high and low TSH groups.…”
Section: Discussionmentioning
confidence: 99%
“…As the nLF and LF/HF ratios are indicators of the relative level of sympathetic activity compared with parasympathetic activity, the SNS is activated more than PNS as the TSH level goes to both ends of the euthyroid TSH range. Brusseau et al [ 51 , 52 ] reported that the nLF and LF/HF ratio increased in hyperthyroid patients with decreased TSH levels, while the nLF and LF/HF ratio increased in hypothyroid patients with increased TSH levels. Although the results of the study did not enlist euthyroid patients, they are consistent with the opposite trend in the nLF and LF/HF ratio in the high and low TSH groups.…”
Section: Discussionmentioning
confidence: 99%
“…в группе пациентов с манифестным гипотиреозом меньший процент пациентов с показателем ци<1,24, по-видимому, обусловлен чрезмерной активностью парасимпатической нервной системы, что также определяет высокий риск сердечно-сосудистых событий. необходимо отметить, что процент случаев показателя ци<1,24 у пациентов в группе субклинического гипотиреоза и группе контроля значимо не отличался [21][22][23].…”
Section: оригинальные исследованияunclassified
“…в исследованиях показано, что пациенты с импSt с самыми низкими значениями SDnn, свидетельствующими о выраженной активации симпатической нервной системы, имели повышенный риск смерти от всех причин и смертности от сердечно-сосудистых заболеваний. однако, как известно, клинические признаки гипотиреоза предполагают гипоактивность симпатической и активацию парасимпатической нервной системы, которая характеризуется снижением частоты сердечных сокращений, снижением сердечного выброса и сократимости сердца, а также возникновением желудочковых нарушений ритма [22]. в литературе нет однозначного мнения о преобладании активности симпатической или парасимпатической звеньев внс при данной сочетанной патологии.…”
Section: Analysis Of Heart Rate Variability Indicators In Patients In...unclassified
“…This modular pleiotropy is supported by the 184 (62%) of 298 associated disorders with at least 3 tissue dysplasia symptoms in S2 ). The occurrence of small fiber neuropathy [12,56] and thyroid dysfunction [S1 Table , [116][117] in EDS (Table S1) and COVID19 [59] along with the many shared joint-muscle and dysautonomia symptoms in…”
Section: Distribution and Nature Of Eds And Covid19-related Genesmentioning
confidence: 99%